Processing of Spatio-Temporal Hybrid Search Algorithms in Heterogenous Environment Using Stochastic Annealing NN Search (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In spatio-temporal database the mixed regions are present in a random manner. The existing work produces the result to create new research opportunities in the area of adaptive and hybrid SLS algorithms. This algorithm develops initialization algorithms which are used only for the homogenous environment. Most current approaches assume, as we have done here, only the homogenous mixtures. Approach: To overcome the above issue, we are going to implement a new technique termed Stochastic Annealing Nearest Neighbor Search using hybrid search algorithms (SANN- HA) for spatio-temporal heterogeneous environment to retrieve the best solution. It provides enhanced fits for definite run length distributions, and would be useful in other contexts as well. Results: Performance of Stochastic Annealing Nearest Neighbor Search using hybrid search algorithms is to discover different sub explanations using different mixture of algorithms in terms of run length distribution and average time for execution based on data objects. Conclusion: It considers the problem of retrieving the high quality solution from the heterogeneous environment. An analytical and empirical result shows the better result with the efficient hybrid search algorithms of our proposed SANN scheme.